Estimation of Factors Affecting Burnout in Greek Dentists before and during the COVID-19 Pandemic - Maria Antoniadou (MDPI AG, 2022)
This study is a comprehensive, cross-sectional survey in occupational burnout, career satisfaction, and quality of life conducted in March 2021 among dentists in the vast area of metropolitan Athens, Greece. Data were collected using a self-reported questionnaire based on the Copenhagen Questionnaire (CQ) for assessing work stress and the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) for evaluating occupational burnout. Using the independent t-test, ANOVA, Pearson's correlation, and multiple linear regression, 804 valid questionnaires were analyzed. During the pandemic, personal exhaustion was affected by gender (b = 1.862, p = 0.0001), age (b = −0.598, p = 0.0001), number of children (b = −0.886, p = 0.020) and higher degree (b = −0.450, p = 0.012). Exhaustion due to working with patients was affected by gender (b = 0.662 p = 0.0001), age (b = −0.513, p = 0.0001), number of children (b = −0.701, p = 0.0001), higher degree (b = −0.207, p = 0.028) and years in practice (b = 0.408 p = 0.0001). Males were more prone to unhappiness, dissatisfaction, and professional physical and emotional exhaustion, but personal resources through higher education, beliefs, values, and hobbies can offer a preventive shield to all dental professionals. Economic management issues can also enhance dentists' satisfaction and feeling of safety in a rapidly changing environment.